Effect of urbanization on the avifauna in a tropical metropolitan area - Biamonte, Estaban (2011)
The rapid and unplanned expansion of urban areas is a common pattern in neotropical developing countries. Urbanization has eliminated or drastically altered large areas of natural habitats used by the rich neotropical avifauna. In our study area, in Costa Rica’s Central Valley, urbanization increased 72% in 33 years with the consequent destruction, fragmentation, and isolation of forest tracts, shade plantations, and other semi-natural habitats used by a rich avifauna. We show that over the last 16 years 32 resident species of birds have disappeared from this area. Species with specialized habitat requirements or particular life history traits (e.g., altitudinal migrants) are disproportionately represented among those birds that have disappeared from the region. Another 34 latitudinal migrants have gone undetected as nearly all habitats these species used as a stopover site during the autumn migration have disappeared; many of these migrants were very abundant 16 years earlier. Relative abundance has also decreased for most resident and migratory species that remained or visited the area. If uncontrolled urban expansion continues, we predict that the rate of extinction of the avifauna that originally inhabited this region would continue possibly increasing.